2001
DOI: 10.1039/b000678p
|View full text |Cite
|
Sign up to set email alerts
|

Celastraceae sesquiterpenoids: biological activity and synthesis

Abstract: Plant extracts of the Celastraceae have been used for centuries throughout South America and China as insect repellents and insecticides in traditional agriculture, and also for the treatment of a plethora of medical ailments from stomach complaints and fever to rheumatoid arthritis and cancer. Many of the medicinally interesting properties associated with these crude preparations have now been attributed to a large family of highly oxygenated sesquiterpenoids based on a tricyclic dihydroagarofuran skeleton. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
149
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(151 citation statements)
references
References 43 publications
0
149
0
2
Order By: Relevance
“…Among the active compounds identified in those extracts are sesquiterpenes, which constitute a wide family of natural compounds with a considerable range of bioactive properties and with potential clinical applications as anticancer drugs, and MDR reversal agents in cancer cells (16) and in the protozoan parasite Leishmania (17,18). Because of these previous findings, we have initiated research to determine the cellular target(s) for sesquiterpenes and to characterize their molecular mechanism of action to rationally design new, more efficient modulators based on their chemical structure.…”
Section: Introductionmentioning
confidence: 99%
“…Among the active compounds identified in those extracts are sesquiterpenes, which constitute a wide family of natural compounds with a considerable range of bioactive properties and with potential clinical applications as anticancer drugs, and MDR reversal agents in cancer cells (16) and in the protozoan parasite Leishmania (17,18). Because of these previous findings, we have initiated research to determine the cellular target(s) for sesquiterpenes and to characterize their molecular mechanism of action to rationally design new, more efficient modulators based on their chemical structure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that sesquiterpenes from the Celastraceae and Euphorbiaceae families could act as reversal agents (Spivey et al, 2002;Madureira et al, 2004). The probable mechanism of feselol action could be its interaction with and inhibition of the function of the MRP2.…”
Section: Discussionmentioning
confidence: 99%
“…Its phytochemistry has been examined and it is known to contain multiple constituents including flavonoids, tannins, alkaloids, triterpenes and sesquiterpenes. 2,12,[32][33][34] However, some studies have shown fatal outcomes after intake of medicinal plants with drugs. For example, concomitant use of warfarin and plants such as ginkgo biloba and ginseng are contraindicated in order to reduce the number of deaths by bleeding.…”
Section: Introductionmentioning
confidence: 99%